2018
DOI: 10.1016/j.ymthe.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Cochlear Hair Cells and Hearing Recovery through Hes1 Modulation with siRNA Nanoparticles in Adult Guinea Pigs

Abstract: Deafness is commonly caused by the irreversible loss of mammalian cochlear hair cells (HCs) due to noise trauma, toxins, or infections. We previously demonstrated that small interfering RNAs (siRNAs) directed against the Notch pathway gene, hairy and enhancer of split 1 (Hes1), encapsulated within biocompatible poly(lactic-co-glycolic acid) nanoparticles (PLGA NPs) could regenerate HCs within ototoxin-ablated murine organotypic cultures. In the present study, we delivered this sustained-release formulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 85 publications
3
35
0
Order By: Relevance
“…In the organ of Corti of adults, however, the activity of the Atoh1, Wnt and the Notch pathway is reduced, and the effects of Notch inhibition by GSI are consequently minimal compared with the neonatal situation (Basch et al, 2016b;Hartman et al, 2009;Maass et al, 2015). Moreover, responsiveness to GSI-treatment in the adult inner ear may depend on damage; expression of Notch downstream effectors increases after trauma, which causes overt hair cell loss (Batts et al, 2009;Du et al, 2018;Mizutari et al, 2013), but not after exposure to noise that induces less extensive hair cell death (Maass et al, 2015). Activation of canonical Wnt signaling though β-catenin stabilization also results in cell cycle re-entry of supporting cells (Li et al, 2015;Roccio et al, 2015;Samarajeewa et al, 2018) and prolongs the time window for GSI-induced hair cell differentiation.…”
Section: Sox2mentioning
confidence: 99%
See 1 more Smart Citation
“…In the organ of Corti of adults, however, the activity of the Atoh1, Wnt and the Notch pathway is reduced, and the effects of Notch inhibition by GSI are consequently minimal compared with the neonatal situation (Basch et al, 2016b;Hartman et al, 2009;Maass et al, 2015). Moreover, responsiveness to GSI-treatment in the adult inner ear may depend on damage; expression of Notch downstream effectors increases after trauma, which causes overt hair cell loss (Batts et al, 2009;Du et al, 2018;Mizutari et al, 2013), but not after exposure to noise that induces less extensive hair cell death (Maass et al, 2015). Activation of canonical Wnt signaling though β-catenin stabilization also results in cell cycle re-entry of supporting cells (Li et al, 2015;Roccio et al, 2015;Samarajeewa et al, 2018) and prolongs the time window for GSI-induced hair cell differentiation.…”
Section: Sox2mentioning
confidence: 99%
“…Although Wnt and Notch pathway components are expressed throughout early (P0) and late (P8) neonatal stages, targets related to cell proliferation and cell cycle progression are downregulated (Samarajeewa et al, 2018). Unlike the results in the newborn cochlea and vestibular organs (Bramhall et al, 2014;Jeon et al, 2011;Lin et al, 2011;McLean et al, 2017;Yamamoto et al, 2006), drugs and siRNAs targeting Wnt and Notch signaling show limited effects in adult models of hearing loss, such as from noise damage (Du et al, 2018;Mizutari et al, 2013;Tona et al, 2014). The generation of new hair cells through Atoh1 overexpression in some animal studies have demonstrated promise for the recovery of hearing (Izumikawa et al, 2005), although others have shown only marginal functional improvements (Atkinson et al, 2014).…”
Section: Sox2mentioning
confidence: 99%
“…The other used guinea pigs as an experimental model, but only tested three animals [ 124 ]. Lastly, siRNA against the NOTCH effector Hes1 have been introduced into the cochleae of guinea pigs after noise exposure [ 125 ]. This intervention drove improvements of 8–12 dB from an initial threshold shift of 60–80 dB, when compared to scrambled RNA controls.…”
Section: Hearing Restoration After Noise Damage In Adult Mammalsmentioning
confidence: 99%
“…Although, the newly generated hair cells exhibit an immature phenotype and lineage-tracing studies are still needed to confirm the origins of these new hair cells. 38 , 39 …”
Section: Main Textmentioning
confidence: 99%
“… 19 , 22 , 23 , 25 , 27 , 28 , 29 , 30 , 31 Given their roles in development, activation of canonical Wnt signaling following birth can promote supporting cell proliferation and limited hair cell induction, and inhibition of the Notch pathway can promote the transdifferentiation of supporting cells to hair cells. 34 , 35 , 36 , 37 , 38 , 39 , 46 , 47 , 49 , 50 , 52 , 53 , 54 , 55 There has been some success in hair cell regeneration following Wnt and Notch modulation in the mature mammalian cochlea. 34 , 52 However, it is important to note that many of these newly generated hair cells show limited survival and do not appear to fully differentiate, lacking mature stereocilia, and they may fail to form proper synaptic connections with auditory neurons.…”
Section: Main Textmentioning
confidence: 99%